Collaborative economy and tourism : perspectives, politics, policies and prospects - Dredge, Dianne; Gyimóthy, Szilvia (Tourism on the verge., 2017)
This book employs an interdisciplinary, cross-sectoral lens to explore the collaborative dynamics that are currently disrupting, re-creating and transforming the production and consumption of tourism. House swapping, ridesharing, voluntourism, couchsurfing, dinner hosting, social enterprise and similar phenomena are among these collective innovations in tourism that are shaking the very bedrock of an industrial system that has been traditionally sustained along commercial value chains. To date there has been very little investigation of these trends, which have been inspired by, amongst other things, de-industrialization processes and post-capitalist forms of production and consumption, postmaterialism, the rise of the third sector and collaborative governance. Addressing that gap, this book explores the character, depth and breadth of these disruptions, the creative opportunities for tourism that are emerging from them, and how governments are responding to these new challenges. In doing so, the book provides both theoretical and practical insights into the future of tourism in a world that is, paradoxically, becoming both increasingly collaborative and individualized.